2007
DOI: 10.1097/01.tp.0000252783.66886.f3
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of Acute and Chronic Graft-Versus-Host Disease in a Murine Model Is Associated with Glucocerebroside-Enhanced Natural Killer T Lymphocyte Plasticity

Abstract: GC ameliorates GVHD in both Th1- and Th2-mediated murine models, suggesting it is able to differentially affect the immune system. GC may alleviate immunologically incongruous disorders, and may be associated with "fine tuning" of immune responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 40 publications
2
26
0
Order By: Relevance
“…iNKTs express a semiinvariant T-cell receptor a chain (Va24Ja18 in human) that recognizes lipids presented by the nonpolymorphic class I-like molecule CD1d. 18 Thus far, the beneficial immunologic effects of iNKTs in the setting of allo-SCT were associated to a decreased incidence of acute GVHD both in experimental models 19,20 and in the clinical setting. Therefore, Chaidos et al reported that PBSC grafts with higher iNKT doses were associated with a significant decrease of aGVHD.…”
Section: Discussionmentioning
confidence: 99%
“…iNKTs express a semiinvariant T-cell receptor a chain (Va24Ja18 in human) that recognizes lipids presented by the nonpolymorphic class I-like molecule CD1d. 18 Thus far, the beneficial immunologic effects of iNKTs in the setting of allo-SCT were associated to a decreased incidence of acute GVHD both in experimental models 19,20 and in the clinical setting. Therefore, Chaidos et al reported that PBSC grafts with higher iNKT doses were associated with a significant decrease of aGVHD.…”
Section: Discussionmentioning
confidence: 99%
“…GC has been shown to function as a 'finetuning factor' in several mouse models of immune-mediated disorders [10,11]. The administration of GC protects against chronic graft-versus-host disease in mice due to an increase in the intrahepatic CD4/CD8 T cell ratio and decreased CD8 + T cell trapping [12]. In addition, in a colitis animal model, GC treatment alters the expression of the ganglioside GM1, a key marker of cell membrane lipid rafts on CD4 + and CD8 + T cells, and alleviates immune-mediated colitis [13].…”
Section: Introductionmentioning
confidence: 99%
“…Solid malignant disorders 49,172 171 Ob/Ob mice 76 Cohen rats 77 Sand rats 78 Autoimmune disorders Acute and chronic graft versus host disease 73 …”
Section: Malignancymentioning
confidence: 99%
“…These data suggest that GC can ameliorate GVHD in both Th1-and Th2-mediated murine models and that it is able to differentially affect the immune system. 73 …”
Section: Graft-versus-host Diseasementioning
confidence: 99%
See 1 more Smart Citation